Mães de anjos e guerreiras : a representação da maternidade de mães de crianças com microcefalia em postagens no Facebook - Vívian Tatiene Nunes Campos (2023)
This research aimed to understand, from an intersectional perspective, how mothers of children with microcephaly represented their experience through posts on a Facebook page created and managed by themselves. The empirical object of the investigation is the page União de Mães de Anjos (UMA) of Pernambuco. As a theoretical and conceptual framework, the research was based on praxiological communication; the transversality between communication and health; and intersectionality. The concept of experience, from Dewey (1980) and Collins (2019a), and that of representation, according to the reflections of Hall (2016) and Borges (2012), were used for the observation and analysis of the material. Reflections on historical conceptions of motherhood and care were essential for the research. While hegemonic feminist authors may portray motherhood as a limiting and oppressive factor, and have the defense of the right to abortion as one of their most important claims, black feminist authors complicate this issue, highlighting other issues and layers of reproductive rights and specificities of motherhood at the crossroads of race, gender and class. In reflecting on the experience of these women, who are mostly black, of childbearing age, impoverished and from the Northeast, we also consider other axes of oppression, bringing discussions about disability and ableism, as well as about environmental racism. In the process of methodological construction, we adopted content analysis as a reference, based on Bardin's proposal (2002), to apprehend our corpus, which was also crossed by the intersectional perspective. As a result of the research, we observed in the framings a resignification of the experience with suffering, configuring motherhood as a divine mission, destined to mothers who are chosen, the mothers of angels. Data showed that the group avoided portraying mothers as vulnerable people, abandoned by their partners, which could reinforce the social stereotype of victimization and further stigmatization. Mothers of children with microcephaly assume a political role through organization, mutual support and claiming their rights to public authorities. The group, in a conservative political-religious context, sought to represent women as mothers of angels and warriors, due to the particularity of caring for children with microcephaly and coping with the physical and emotional overload related to this work and this function, understood by them as a mission.